Evaluating pretreatment serum CA-125 levels as prognostic biomarkers in endometrial cancer: a comprehensive meta-analysis - Yu, Zhong; Sun, Yue (Frontiers in Oncology, 2024)
BackgroundIn recent years, the incidence of endometrial cancer (EC) has been rising. This meta-analysis aims to clarify the prognostic significance of serum CA-125 levels in EC.MethodsArticles up to March 1, 2024, were systematically searched in EMBASE, Cochrane Library, PubMed, and Web of Science. This analysis pooled hazard ratios (HR) and 95% confidence intervals (CI) from qualifying studies to evaluate the association of CA-125 levels with overall survival (OS), progression-free survival (PFS), disease-free/relapse-free survival (DFS/RFS), and disease-specific survival (DSS).Results25 studies involving 7,716 patients were included. The analysis revealed that elevated CA-125 levels correlate with poorer OS (HR = 1.848, 95% CI: 1.571-2.175, p < 0.001). This association persisted across various study regions and sample sizes, and was notably strong in subgroups with a CA-125 cut-off value of less than 35 (HR = 2.07, 95% CI: 1.13-3.80, p = 0.019) and equal to 35 (HR = 2.04, 95% CI: 1.49-2.79, p < 0.001), and among type II pathology patients (HR = 1.72, 95% CI: 1.07-2.77, p = 0.025). Similarly, high CA-125 levels were linked to reduced PFS, particularly in subgroups with a CA-125 cut-off value less than 35 (HR = 1.87, 95% CI: 1.15-3.04, p = 0.012) and equal to 35 (HR = 4.94, 95% CI: 2.56-9.54, p < 0.001), and in endometrioid endometrial cancer patients (HR = 2.28, 95% CI: 1.18-4.40, p = 0.014). Elevated CA-125 levels were also indicative of worse DFS/RFS (HR = 2.17, 95% CI: 1.444-3.262, p < 0.001) and DSS (HR = 2.854; 95% CI: 1.970-4.133, p < 0.001).ConclusionSerum CA-125 levels before treatment was highly associated with prognosis of EC patients.